Prevalence of Overweight and Obesity Among Children and Adolescents With Autism Spectrum Disorder and Associated Risk Factors - Kamal Nor, Norazlin; Ghozali, Azilawati Hanim; Ismail, Juriza (Frontiers in Pediatrics, 2019)
Introduction: Prevalence of obesity in Autism Spectrum Disorder (ASD) has been reported to be higher than in the general population. Determining prevalence may help increase awareness of obesity in ASD and potentially lead to initiatives to reduce obesity. In order to understand obesity in ASD children, common risk factors for obesity were assessed including physical activity, feeding problems and sleep disturbances. Methods: This is a cross-sectional study performed at the Child Development Center at Universiti Kebangsaan Malaysia Medical Center on 151 ASD children aged 2 to 18 years. Anthropometric and demographic information were obtained and parents completed three questionnaires; Children Sleep Habits Questionnaire (CSHQ), Physical Activity for Older Children Questionnaire (PAQ-C) and Brief Autism Mealtime Behaviour Questionnaire (BAMBI). Results: For ASD children in our sample, the prevalence of overweight (BMI ≥85th to <95thpercentiles) was 11.3% and the prevalence of obesity (BMI ≥95thpercentile) was 21.9%. The overweight/obese ASD children’s median age was higher at 8.5 years (IQR 5.81-10.13) compared to normal/underweight group of 6.33 years (IQR 4.75–7.7) with p-value of 0.001. The two groups also differed significantly for maternal BMI and paternal age. The median maternal BMI in the overweight/obese group was 26.05 (IQR 23.35-32.25), statistically significantly higher (p=0.003) than in the non-overweight/obese group, 24.7 (IQR 21-27.9). The median paternal age of 40 years (IQR 37-44) was statistically significantly higher (p=0.039) in the overweight/obese group, compared to the median paternal age in the non-overweight/obese group of 38 (IQR 35-42). The male overweight/obese children had median PAQ-C score of 2.44 (IQR 2.00-3.00) versus 2.89 (IQR 2.35-3.53) in the counterpart group with p-value of 0.01. Using multiple linear regression stepwise method, three predictors associated with BMI percentiles reached a statistical level of significance; PAQ-C score in males (p<0.001), the BAMBI domains of Food Refusal (p=0.001) and Limited Variety of Food (p=0.001). Conclusions: The prevalence of obesity and overweight is high among Malaysian ASD children and adolescents. Older child age, high maternal BMI, older paternal age, low physical activity and low likelihood of food refusal and high likelihood of food selectivity were found to be risk factors for high BMI in these children.